2017
DOI: 10.3389/fnhum.2017.00463
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Word Learning through Repetition and Imitation: Functional Networks as a Function of Learning Phase and Language Distance

Abstract: Introduction and Aim: Repetition and imitation are among the oldest second language (L2) teaching approaches and are frequently used in the context of L2 learning and language therapy, despite some heavy criticism. Current neuroimaging techniques allow the neural mechanisms underlying repetition and imitation to be examined. This fMRI study examines the influence of verbal repetition and imitation on network configuration. Integration changes within and between the cognitive control and language networks were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 89 publications
1
18
0
Order By: Relevance
“…It was only the intervention group that yielded significant improvement results in both functional and behavioral measures after the intervention of the language class. In addition, FLL studies conducted among adult learners show that certain teaching methods, such as repetition, imitation, and drilling, can have a positive impact on higher network configuration (Ghazi-Saidi and Ansaldo, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was only the intervention group that yielded significant improvement results in both functional and behavioral measures after the intervention of the language class. In addition, FLL studies conducted among adult learners show that certain teaching methods, such as repetition, imitation, and drilling, can have a positive impact on higher network configuration (Ghazi-Saidi and Ansaldo, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…• Descriptive studies (Panitsides, 2014); studies not focusing on the research topic, including the studies on bilingualism (Small et al, 1999;Friebe and Schmidt-Heartha, 2013;Clare et al, 2014;Zahodne et al, 2014;Narushima et al, 2018); studies having different age of the subjects (Schlegel et al, 2012;Bak et al, 2016;Ghazi-Saidi and Ansaldo, 2017); and review studies (Antoniou et al, 2013;Klimova, 2018) were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…As far as learning English is concerned, participants had some difficulties with the retention of new words, which is quite common at this age [ 30 ]. This shortcoming can be overcome by regular revision and practicing of new words and phrases [ 31 ], as well as by different teaching and learning strategies, e.g., repetitive, drill-like training, or creating associations [ 13 , 32 ], which may positively affect their higher network configuration [ 33 ]. Attending the course regularly every Wednesday and doing homework also helped the participants enhance their executive skills, such as organizing their everyday schedule more efficiently, as well as concentrating on tasks better.…”
Section: Discussionmentioning
confidence: 99%
“…If participants typed the collocation exactly as it was shown, the collocation was displayed in blue font; otherwise, the correct collocation appeared in red font (see Figure 1). Overt vocal repetition was used because it has been suggested that it aids learning (e.g., Ghazi-Saidi & Ansaldo, 2017); typed responses allowed to provide automatized feedback during this phase.
Fig.
…”
Section: Methodsmentioning
confidence: 99%